Awareness and Use of Library Facilities and Services by the Research Scholars in the Universities in Karnataka: an Analytical Study - Gowda, Vasappa; Shivalingaiah, D. (Journal of Information and Knowledge, 2013)
Information is an essential commodity for research. University libraries provide information to the research. In the present study an attempt was made to know the library facilities and services required by the research scholars in the traditional universities in Karnataka State. Survey method using questionnaire as an instrument was adopted to collect data. SPSS tool was used for data analysis. The research scholars’ responses on awareness and satisfaction level on various library facilities and services were gathered using Likert’s 5 point scale. The responses were analysed using two way ANOVA, Tukey HSD, Factor Analysis and Fisher’s Exact Test. The analysis showed that for majority of the humanities and social science respondents, the facilities and services available in the university libraries were poor whereas the science respondents opined that the facilities and services were moderately good. The hypotheses formulated in this connection were partially proved by the study. Results showed that there were significant differences in the satisfaction level of facilities and services among the research scholars of various disciplines.